The silicon regulates microbiome diversity and plant defenses during cold stress in Glycine max L. - Ahmad, Waqar; Coffman, Lauryn; Weerasooriya, Aruna D; Crawford, Kerri; Khan, Abdul Latif (Frontiers in Plant Science, 2024)
Introduction With climate change, frequent exposure of bioenergy and food crops, specifically soybean (Glycine max L.), to low-temperature episodes is a major obstacle in maintaining sustainable plant growth at early growth stages. Silicon (Si) is a quasi-essential nutrient that can help to improve stress tolerance; however, how Si and a combination of cold stress episodes influence plant growth, plant physiology, and microbiome diversity has yet to be fully discovered. Methods The soybean plants were exposed to cold stress (8-10°C) with or without applying Si, and the different plant organs (shoot and root) and rhizospheric soil were subjected to microbiome analysis. The plant growth, physiology, and gene expression analysis of plant defenses during stress and Si were investigated. Results and discussion We showed that cold stress significantly retarded soybean plants’ growth and biomass, whereas, Si-treated plants showed ameliorated negative impacts on plant growth at early seedling stages. The beneficial effects of Si were also evident from significantly reduced antioxidant activities – suggesting lower cold-induced oxidative stress. Interestingly, Si also downregulated critical genes of the abscisic acid pathway and osmotic regulation (9-cis-epoxy carotenoid dioxygenase and dehydration-responsive element binding protein) during cold stress. Si positively influenced alpha and beta diversities of bacterial and fungal microbiomes with or without cold stress. Results showed significant variation in microbiome composition in the rhizosphere (root and soil) and phyllosphere (shoot) in Si-treated plants with or without cold stress exposures. Among microbiome phyla, Proteobacteria, Bacteroidota, and Ascomycota were significantly more abundant in Si treatments in cold stress than in control conditions. For the core microbiome, we identified 179 taxa, including 88 unique bacterial genera in which Edaphobacter, Haliangium, and Streptomyces were highly abundant. Enhanced extracellular enzyme activities in the cold and Si+cold treatments, specifically phosphatase and glucosidases, also reflected the microbiome abundance. In conclusion, this work elucidates cold-mediated changes in microbiome diversity and plant growth, including the positive impact Si can have on cold tolerance at early soybean growth stages – a step toward understanding crop productivity and stress tolerance.